Frontispiece: Making a Splash in Homogeneous CO2 Hydrogenation: Elucidating the Impact of Solvent on Catalytic Mechanisms. Issue 64 (20th November 2018) - Wiedner, Eric S.; Linehan, John C.
Abstract : The solvent can have a profound impact on homogeneous catalysis through its interactions with the catalyst, reactants, and products. As a result, the solvent can become a controllable parameter of rational catalyst design by understanding how different solvents participate in catalysis. In their Minireview onpage 16964 ff., E. S. Wiedner and J. C. Linehan highlight recent progress in understanding the impact of the solvent identity on hydrogenation of CO2 by molecular catalysts.